UHPLC-MS/MS-GNPS based phytochemical investigation of Dryopteris ramosa (Hope) C. Chr. and evaluation of cytotoxicity against liver and prostate cancer cell lines - Zia-ur-Rehman; Hafiz Majid Rasheed; Kashif Bashir; Aleksandra Gurgul; Fazli Wahid; Chun-Tao Che; Irum Shahzadi; Taous Khan (Heliyon, 2022)
Dryopteris ramosa (family; Dryopteridaceae) has been reported for its medicinal importance in cancer, gastrointestinal disorders, and infections. The present study aimed to investigate the detailed phytochemical profile of D. ramosa and its cytotoxic potential using various cancer cell lines. The phytochemical profile of D. ramosa methanolic extract and its fractions were established by employing UHPLC-MS/MS and Global Natural Product Social (GNPS) molecular networking. Moreover, the cytotoxic activity of extract and fractions was evaluated against human liver (HepG-2) and prostate cancer (PC-3) cells using MTT assay. Overall, 18 compounds including flavonoids, flavonoid O-glycosides, isoflavone di-C-glycoside, flavanol, flavanone, rotenoid, phloroglucinol derivative, coumarin derivative, benzofuranone, abietic acid, and phenolic acid were observed as the major phytochemical bioactive constituents in the extract and fractions of D. ramosa. In MTT assay, chloroform fraction showed highest anti-proliferative activity against liver cancer cells (IC50 = 53.49 μg/mL) followed by n-hexane fraction (IC50 = 55.36 μg/mL), D. ramosa extract (IC50 = 85.67 μg/mL) and ethyl acetate (IC50 = 125.00 μg/mL) fraction. However, n-hexane and chloroform fractions presented maximum cytotoxic effect against prostate cancer cells with respective IC50 values of 214.53 and 281.47 μg/mL. Moreover, all the tested samples showed negligible toxicity against non-cancer (BHK-21) cells. The results indicated that D. ramosa is rich in flavonoids, phloroglucinol derivative, and phenolic acids and showed positive results in cytotoxic studies, especially against liver cancer. Therefore, it can be considered safe for the development of anticancer drugs, especially against liver cancer.